Estudio alimentario tradicional para impulsar la agroindustria en la comuna Collana Catacocha - Rosillo Guarnizo, Ligia Elizabeth (2014)
The territory of the Commune Collana Catacocha is altitudinally differential among 1000 - 2200 meters, geographically consists of sloping ground, the temperature ranges from 16 to 22oC, have a land area of 7770 hectares, the communal territory was divided into two Agro-Ecological Zones (High and Media) and appeared in 11 communities in the Commune, which houses a large agrobiodiversity especially for the amount of edible plants and animals. Through research it was possible to analyze one of the existing problems in the Commune. It is the little revenue they receive from selling their products, that is why it is necessary to give them an extra value developing ancestral foods, using the knowledge of the community and new technologies. Among the main results we found that the dominant plant species in the Commune are corn 16.2%, beans 15.4%, peanuts 12.3%, zarandaja 10.9%, pumpkin 10.1%, peas 9.9% and sweet potato 7.7% and the animal species there are chickens 45%, pork 26%, guinea pigs 13%, those are used for the production of selected products for industrialization. For processing that we perform in the CBFT plant, six foods were selected where three formulations were practiced, which the most accepted by the people who tasted the sarandaja flour was chose was selected second toasting time, was selected bean salad stick the third formulation, Molloco third formulation, grooms chicha third formulation, sweet pumpkin, sausage third formulation. Finally a market study was made where it was known that the six ancestral foods have good acceptance in the Loja market by 75.18% would be willing to buy and a 79.78% in Catacocha would be willing to buy them, that corroborates that it is feasible to implement a productive project in the Commune for the industrialization of their products.